First record of Colombian Forest Mouse Chilomys instans (Cricetidae: Rodentia) in Cajamarca: updating the list of mammals from Peru - Medina, César E. (2016)
Chilomys instans (Thomasomyini, Cricetidae) is a common species in the mammalian fauna that inhabits in the Northern Andes of South America. Here we present the first record of that in Peru, based on the morphologic review of three samples collected in Cajamarca Department (Central Andes). Information about the taxonomic and natural history of C. instans are presented. The wide distribution of genus Chilomys in Andes shows the necessity to perform a taxonomic review of the genus, in order to clearify the species limit.